2016
DOI: 10.1016/j.tranpol.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ responses to proposed highway projects: Exploring the role of governmental information provision

Abstract: Despite increased efforts to actively consult residents in highway infrastructure planning to i.a. increase acceptance of plans, the involvement of most residents is passive and limited to receiving information. By means of multivariate regression analysis, this paper explores the role of governmental information provision in residents' responses towards highway project proposals, measured by the expected change in residential satisfaction i.e. the match between housing needs and conditions, as a consequence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…A similar situation applies to the concepts of "positive expectations towards future" or "positive future expectation". It is seen that this concept has been used in different research areas and conceptually in a totally different contexts such as the degree of positiveness of the individual's expectations about his / her own personal future (Callina et al 2014;Eryılmaz, 2011;Schmid et al, 2011;Zhou and Lu, 2011), positive expectations about the future firm competitions (Hansen, 2003) or the positive impact of the project team on obtaining information (Hamersma et al, 2016). The literature review and their results revealed that these two concepts (at least in the sources that are put forward and used) are used only superficially without any definition; in other words, they do not have a conceptual framework and a systematized theoretical infrastructure.…”
Section: Theoretical Background Of the Concept Of Self-expectation Fomentioning
confidence: 99%
See 1 more Smart Citation
“…A similar situation applies to the concepts of "positive expectations towards future" or "positive future expectation". It is seen that this concept has been used in different research areas and conceptually in a totally different contexts such as the degree of positiveness of the individual's expectations about his / her own personal future (Callina et al 2014;Eryılmaz, 2011;Schmid et al, 2011;Zhou and Lu, 2011), positive expectations about the future firm competitions (Hansen, 2003) or the positive impact of the project team on obtaining information (Hamersma et al, 2016). The literature review and their results revealed that these two concepts (at least in the sources that are put forward and used) are used only superficially without any definition; in other words, they do not have a conceptual framework and a systematized theoretical infrastructure.…”
Section: Theoretical Background Of the Concept Of Self-expectation Fomentioning
confidence: 99%
“…In some of the studies in the literature on similar concepts, it is noteworthy that organizational management interferes with the expectations of individuals consciously (Portoghese et al, 2012;Hamersma et al, 2016). However, SEOI represents the expectations that totally occur spontaneously in the mind of the individual without any conscious and planned intervention by the organization management, and their hopes on certain issues regarding the future.…”
Section: Spontaneous Formationmentioning
confidence: 99%
“…Residents' responses to government project proposals depend on their perceptions of its benefits and costs, and the tradeoffs between them (Hamersma, Heinen, Tillema, & Arts, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the provided involvement activities, studies also show that residents vary in their preference for degree of involvement; some groups of residents prefer to be more deeply involved in government decision-making (Bickerstaff and Walker 2001;Diduck and Sinclair, 2002;Hamersma et al 2016). In addition, research suggests that contextual factors such as cultural aspects, historical events, and personal (socioeconomic or attitudinal) factors may influence the way in which involvement activities of governments are perceived by residents (Luyet et al 2012;Stenseke 2009;Irvin and Stansbury 2004;Chi, Xu, and Xue 2014;Webler, Tuler, and Krueger 2001;Hanna 2016;Hamersma et al 2016). To better understand the effectiveness of involvement activities with residents, it therefore also seems important to account for personal contextual factors.…”
Section: Introductionmentioning
confidence: 99%